Branding in the era of artificial intelligence (AI): an examination of hybrid human-AI approach in the rebranding of citizenLab - Sacramento, Isabela Berger (2023)
This research investigates Artificial Intelligence (AI) and branding in relation to the rebranding process at the Belgian civic tech company, CitizenLab. Using different AI tools such as OpenAI’s ChatGPT, this study explores how the ability of AI to emulate and improve traditional branding phases such as interviewing stakeholders, producing brand concepts, and developing a visual identity. The significant benefits of using AI for speed and scalability are displayed and limitations are further uncovered, particularly in capturing cultural nuances and matching the creative and emotional intelligence of human experts. A hybrid model of branding presents the advantages of AI capabilities coupled with human insight to create compelling and efficient branding strategies.